History and Management Zakat in Indonesia - Tahir, Ibrahim Ako; muin, rahmawati . (Islamic Economic and Business Journal, 2023)
Indonesia as a country with the largest Muslim population in the world, of course, requires paying Zakat according to the pillars of Islam. Since ancient times, zakat has been believed by Muslims as a solution to alleviating poverty. This is evidenced from history during the caliphate of Umar bin Abdul Aziz. In historical records it is told that at that time it was difficult to find mustahik (especially the poor) who were entitled to receive zakat. The success of Umar bin Abdul Aziz in managing zakat is inseparable from the strategy or method of managing zakat. At that time, zakat was managed by the government. So that zakat assets are really well distributed. As a result, the people at that time lived in prosperity. The success in the management of zakat during the time of Umar bin Abdul Aziz should have been used as a guide by the Indonesian government in efforts to alleviate poverty. These efforts can be seen from time to time, both from the period of the Islamic empire, the colonial period, the old order period (early independence, the new order, to the reformation era).